Continuous Positive Airway Pressure-Mandibular Advancement Device Combination Therapy for Moderate-to-Severe Obstructive Sleep Apnea: A Preliminary Study - Premaraj, Thyagaseely Sheela; Stadiem, Jacob; Premaraj, Shyamaly Arya; Davies, Charles R.; Dennis, Matthew; Harrington, John J. (European Journal of Dentistry, 2021)
Objectives The purpose of this pilot study was to determine whether compliance to auto-adjusting positive airway pressure (APAP) improves with the addition of a mandibular advancement device (MAD). Secondary outcome measures included were APAP pressure, subjective daytime sleepiness, apnea–hypopnea index (AHI), and mask leaks.Setting and Sample Population Participants included were diagnosed with moderate-to-severe obstructive sleep apnea (OSA) and became noncompliant to prescribed APAP. Thirteen participants with a mean age of 61.6 years were recruited for this study.Materials and Methods All participants were given a MAD to use with their APAP. Parameters measured included APAP pressure, AHI, mask leak reported via ResMed AirViewTM software, and self-reported daytime sleepiness (Epworth Sleepiness Scale [ESS]). A paired two-sample for mean t-test was performed to determine significance.Results The mean difference of pre- and postintervention APAP compliance was 23.1%, which was statistically significant (p = 0.015). The mean APAP air pressures were unchanged. The difference between pre- and postintervention mean ESS scores was 1.4 and was statistically significant (p = 0.027). The mean difference between pre- and postintervention AHI values and mask leak showed no significant difference.Conclusion This study showed that combination of APAP-MAD therapy, for patients with moderate-to-severe OSA who were noncompliant to APAP use, significantly increased compliance with APAP therapy, and significantly decreased the daytime sleepiness of participants.
Keywords: auto-adjusting positive airway pressure; Epworth Sleepiness Scale scores; mandibular advancement device; obstructive sleep apnea